Trust and Tax Compliance in Indonesia - Dewi Prastiwi; Nadya Ramadhani Endrasti; Yuni Khoirotul Abdiyah (Universitas Pendidikan Indonesia, 2024)
This study examines the effect of trust on taxpayer compliance and the potential of gender to moderate this relationship. A quantitative approach was employed using the Structural Equation Modeling (SEM) and SmartPLS tools. The sample size for this research consisted of 400 respondents, and data collection was carried out through a survey. The results indicated that trust enhances taxpayer compliance. However, gender does not moderate this relationship, as the level of trust is influenced not by gender characteristics but by the outcomes experienced by taxpayers in fulfilling their tax obligations. This study's findings also provide empirical evidence supporting the Slippery Slope Framework hypothesis, which asserts that actions should be taken to enhance the authority's power and build taxpayer trust to achieve tax compliance. The practical implication of these findings is that tax authorities should focus on building and maintaining trust with taxpayers to enhance compliance. This can be achieved through transparent, fair, and efficient tax administration practices. Tax authorities can foster a positive image and increase taxpayer trust by improving service quality and demonstrating the proper utilization of tax revenues for community benefits. The sociological approach used in formulating research variables distinguishes this study from others.